Owning the Caribbean: Sustainable development, innovation and entrepreneurship - Urdine Darius (Revista Educación Superior y Sociedad (ESS), 2019)
This article entitled “Owning the Caribbean: sustainable development, innovation and entrepreneurship” was written within the framework of the first Caribbean Youth Forum organized by Caribbean Universities in November 2018. This is a comparative study between the young people of Martinique and Saint Lucia to demonstrate their degree of participation in the environmental policy of their respective countries. To what extent can education about sustainable development and strategies for resistance to climate change be an important element to improve the environment of these Caribbean islands? Urdine Darius analyzes the solutions proposed by young entrepreneurs and asks about the strategies to be implemented for a more innovative management of the environment in Martinique and Saint Lucia.